2022
DOI: 10.1111/1365-2435.14054
|View full text |Cite
|
Sign up to set email alerts
|

Yeast and fruit fly mutual niche construction and antagonism against mould

Abstract: 1. A goal in insect-microbe ecology is to understand the mechanisms regulating species associations and mutualistic interactions.2. The spotted wing drosophila Drosophila suzukii develops in ripening fruit, unlike other drosophilids that typically feed on overripe fruit, and is associated with the yeast Hanseniaspora uvarum.3. We hypothesized that D. suzukii and H. uvarum engage in niche construction leading to a mutualistic relation, facilitating the exploitation of fruit and berries as larval substrate.4. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 186 publications
(218 reference statements)
1
7
0
Order By: Relevance
“…In addition, moulds (filamentous fungi), an important competitor of Drosophila larvae (Wertheim et al 2002;Trienens et al 2010), generally exhibit better growth in a lower pH environment (Zhao et al 2020). This could have led to a lower attractiveness for D. suzukii in our study, as decreased egg deposition in response to grey mould (Botrytis cinerea) was observed in a recent study (Chakraborty et al 2022).…”
Section: What Influences Attacks On the Forest Plants Studied?supporting
confidence: 48%
“…In addition, moulds (filamentous fungi), an important competitor of Drosophila larvae (Wertheim et al 2002;Trienens et al 2010), generally exhibit better growth in a lower pH environment (Zhao et al 2020). This could have led to a lower attractiveness for D. suzukii in our study, as decreased egg deposition in response to grey mould (Botrytis cinerea) was observed in a recent study (Chakraborty et al 2022).…”
Section: What Influences Attacks On the Forest Plants Studied?supporting
confidence: 48%
“…Adult and larval stages of D. suzukii showed a preference for the yeast H. uvarum on food sources. [85][86][87][88] Hanseniaspora uvarum also increases the fecundity of female D. suzukii. 89 Drosophila suzukii female laid more eggs on H. uvarum-inoculated blueberries and are more attracted to H. uvarum volatiles compared to volatiles of S. cerevisiae or Pichia terricola.…”
Section: The Role Of Microbes In Affecting D Suzukii Behaviour and In...mentioning
confidence: 98%
“…Adult and larval stages of D. suzukii showed a preference for the yeast H. uvarum on food sources 85–88 . Hanseniaspora uvarum also increases the fecundity of female D. suzukii 89 .…”
Section: The Role Of Microbes In Affecting D Suzukii Behaviour and In...mentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate these assumptions, D. melanogaster flies were mono-associated with H. uvarum. Based on previous studies (Chakraborty et al, 2022;Chandler et al, 2012;Hamby et al, 2012), H. uvarum in particular appears to be widespread and common in Drosophila populations, which is why we generated gnotobiotic flies with H. uvarum in all other experiments conducted in this study. To achieve mono-association, axenic D. melanogaster larvae were individually raised in 2 mL polypropylene micro-vials filled with 1 mL sterile artificial rearing medium.…”
Section: The Crop As a Potential Storage Organ Of Symbiotic Yeast Fungimentioning
confidence: 99%